El presupuesto participativo y su incidencia en la Calidad de gasto público de la Municipalidad distrital de Soritor en el periodo 2013 - 2014” - Fernández Centurión, Hipólito (2016)
The participatory budget is that citizen participation mechanism by which the population contributes to determine the allocation of public resources of the municipality; in fact, the participatory budget is a form of participatory democracy in governance. This citizen involvement, through the participatory budget, is intended to be transparent municipal management and propose the execution of public spending, which is the amount of financial, material and human resources that the public sector represented by the government employs to fulfill its functions primarily benefit the district's population. The aim of this research was to determine how the participatory budget affects the quality of public expenditure of the district municipality of Soritor during the period 2013-2014. To achieve this purpose, we worked with the actors involved to settle the participatory budget of the district municipality of Soritor; representatives of grassroots organizations, from whom, through surveys, information was collected to determine the effect of the mechanism of municipal management in the quality of public spending. The results obtained showed the public participation in these processes and the perception of the players involved on the implementation of public spending on investment projects related mainly to social programs; further demonstrating the transparency with which the municipal administration is performed during the study period. As part of the conclusions, we might mention that a large percentage (55%9 of the players involved consider that the resources of the district municipality of Soritor are distributed evenly across the population.